Pengaruh Perceived Organizational Support (POS) Terhadap Komitmen Organisasional Dengan Kepuasan Kerja Sebagai Variabel Mediasi Pada Perawat RSUD Dr. Rasidin Padang - Nabila Dasri Vigazi; Rino Rino (Universitas Negeri Padang, 2023)
This study aims to determine the effect of perceived organizational support (POS) on organizational commitment with job satisfaction as a mediating variable for nurses at RSUD dr. Rasidin Padang. This type of research is causative descriptive. This research was conducted on nurses at RSUD dr. Rasidin Padang. When the research was conducted in 2022. The population in this study were nurses at RSUD dr. Rasidin Padang with a sample of 86 nurses taken by cluster random sampling. The data from this study were processed using the help of the SmartPLS3 application. Perceived organizational support (POS) had a positive and significant effect on organizational commitment, job satisfaction had a significant positive effect on organizational commitment, and job satisfaction had a significant positive effect on organizational commitment. Additionally, job satisfaction had a significant positive effect on organizational commitment. Significant impact on job satisfaction and organizational commitment.